NETosis Secondary to the Use of Levamisole-Adulterated Cocaine: A Likely Underlying Mechanism of Vasculopathy (2024)
ABSTRACT: Background. Since 2010, several cases of a new vasculopathy induced by the use of levamisole-adulterated cocaine (LAC) have been reported. This vasculopathy is characterized by retiform purpura, earlobe necrosis, multisystem compromise, and multiple autoantibodies. Given its similarity to antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis, LAC-associated vasculopathy is postulated to be mediated by pathophysiologic processes resulting from neutrophil cell death by NETosis, a phenomenon previously described in ANCA vasculitis. This study tries to establish the presence of NETosis induced by cocaine, levamisole, or both. Methodology. Neutrophils were isolated from the peripheral blood of healthy controls by Ficoll-Hystopaque density gradient centrifugation followed by dextran sedimentation. Cell viability and purity were evaluated by flow cytometry after staining with PI/DiOC6 and labeling with fluorescent anti-CD45/anti-CD3 monoclonal antibodies (mAbs), respectively. Neutrophils were exposed to levamisole, cocaine, a cocaine-levamisole mixture, and sera pools from healthy controls and patients with LAC-associated vasculopathy. NETosis was then assessed by flow cytometry after staining cells with Sytox Green, Hoechst-33342, and fluorescent antineutrophil elastase (NE) and antimyeloperoxidase (MPO) mAbs. In addition, NETosis was morphologically confirmed by fluorescence microscopy. Proinflammatory cytokine levels in culture supernatants and reactive oxygen species (ROS) synthesis were determined by flow cytometry. The involvement of calcium and muscarinic receptors in cell death induction was evaluated in parallel experiments carried out in the presence of 1,2-bis (o-aminophenoxy) ethane-N, N, N′, N′-tetraacetic acid (BAPTA) and hyoscine butylbromide (HBB), their respective inhibitors. Results. Cocaine, levamisole, and a cocaine-levamisole mixture induced neutrophil cell death. DNA/MPO extrusion and cell morphology patterns were consistent with NETosis. Neither proinflammatory cytokines nor ROS behaved as proNETotic factors. Preliminary results suggested that muscarinic receptors and calcium-dependent signals were involved in LAC-induced NETosis. Conclusions. Cocaine, levamisole, and a cocaine-levamisole mixture can induce NETosis through mechanisms involving muscarinic receptors and calcium-dependent pathways.